ChemInform Abstract: A Selective Palladium‐Catalyzed Carbonylative Arylation of Aryl Ketones to Give Vinylbenzoate Compounds. Issue 19 (18th April 2013) - Schranck, Johannes; Tlili, Anis; Neumann, Helfried; Alsabeh, Pamela G.; Stradiotto, Mark; Beller, Matthias
Abstract It provides a straightforward method to prepare (Z)‐vinylbenzoates.